A Comparative Analysis of Cyber Security Laws and Policies in Nigeria and South Africa (Law Research Review Quarterly, 2022)
There is free flow of information in the cyberspace and as a result, nations are obviously wary of the integrity of its data as part of both public safety and national security concerns. There are ways that the associated risk could be mitigated and mostly has to do with a proper development and implementation of Cyber security policies and strategies. This research focuses on the cyber security policies, strategies and laws of both Nigeria and South Africa and also making a comparative analysis of the current National Cyber Security Policy and Strategy of both countries and the necessary recommendations going forward. In the case of Nigeria, analytical evidence shows that the national documents were found to have satisfied most of the requirements in terms of content, but failed to address other aspects of cyber security concerns in the country. On the other hand, South Africa as a country is lagging especially in governmental coordination, cybersecurity legislation, engagement with business and citizens, and skilled labour. The paper tends to explore these loopholes evident in the cyber security laws and policies of the aforesaid countries, and made the necessary recommendations on how to adopt best and sustainable practices in dealing with issues related to cyber security breaches including cybercrime in both countries.